Natural area tourism ecology, impacts, and management - Newsome, David 1951- (Aspects of tourism, 2001)
This text covers all the facets of tourism in natural areas. It is underpinned by a strong foundation of environmental understanding. It then describes the range of impacts, which occur when tourism takes place in the natural environment and illustrates how managers can plan, develop and appropriately manage tourism developments in natural areas. Finally, the book addresses ongoing management concerns such as monitoring environmental change and the need to introduce appropriate management strategies.